Aboriginal and Torres Strait Islander LGBTQA+ Experiences Factsheet 6: Mental health among Aboriginal and Torres Strait Islander LGBTQA+ adults - Darcy Wallis; Kris Wilson; Natalie Amos; Ashleigh Lin; Adam Bourne; Shakara Liddelow-Hunt; Private Lives 3 Study Team; Writing Themselves In 4 Study Team; Trans Pathways Study Team (2024)
Between 2017 and 2020, several national surveys of LGBTQA+ people across Australia were conducted by the Telethon Kids Institute and by ARCSHS. These included: Trans Pathways : a study of gender diverse young people and their mental health and care pathways Private Lives 3 : a study of health and wellbeing among LGBTQ+ adults (aged 18+) Writing Themselves In 4 : a study of health and wellbeing among LGBTQA+ young people (aged 14-21) Each of these studies heard from some LGBTQA+ people who were also Aboriginal and Torres Strait Islander. In order to highlight their specific and unique experiences, this project sought to draw together the responses from these LGBTQA+ Aboriginal and Torres Strait Islander people. Findings from these responses are presented in a series of factsheets. This factsheet explores experiences of mental ill-health, suicidality and support seeking amongst Aboriginal and Torres Strait Islander LGBTQA+ participants in the Private Lives 3 survey.